Interpretation on Management Guideline for the Off-label Use of Drugs in China(2021 Edition) - ZUO Wei; LIU Rongji; SUN Yajia; ZHANG Bo; CHEN Yaolong; ZHANG Shuyang (Xiehe Yixue Zazhi, 2023)
Off-label drug use represents a reasonable need for diagnosis and treatment in some cases, but it faces potential risks with drug safety and legal challenges. However, there was no guideline on how to manage the off-label drug use in China. Therefore, Peking Union Medical College Hospital, in cooperation with Evidence-based Medicine Center of Lanzhou University, established a working group and an expert group consisting of multidisciplinary group of experts to develop the Management Guideline for the Off-label Use of Drugs in China (2021). The Guideline is guided by the Law on Doctors of the People's Republic of China and the World Health Organization Guideline Development Manual. This is the first management guideline on the off-label use of drugs, aiming to improve the stakeholders' understanding of this topic and establish a standardized management procedure in China. This guideline has determined nine questions and proposed a total of twenty-three recommendations. The English version of the guideline was published in September 2022. This paper offers a detailed interpretation of the key points of the guidelines in order to provide suggestions and references for the management of off-label drug use.